WISDOM project - XI. star formation efficiency in the bulge of the AGN-host Galaxy NGC 3169 with SITELLE and ALMA - Lu, Anan; Boyce, Hope; Haggard, Daryl; Bureau, Martin; Liang, Fu-Heng; Liu, Lijie; Choi, Woorak; Cappellari, Michele; Chemin, Laurent; Chevance, Mélanie; Davis, Timothy A; Drissen, Laurent; et al. (Monthly notices of the Royal Astronomical Society, 2022)
The star formation efficiency (SFE) has been shown to vary across different environments, particularly within galactic starbursts and deep within the bulges of galaxies. Various quenching mechanisms may be responsible, ranging from galactic dynamics to feedback from active galactic nuclei (AGNs). Here, we use spatially resolved observations of warm ionized gas emission lines (Hβ, [O iii] λλ4959,5007, [N ii] λλ6548,6583, Hα and [S ii] λλ6716,6731) from the imaging Fourier transform spectrograph SITELLE at the Canada-France-Hawaii Telescope (CFHT) and cold molecular gas (12CO(2-1)) from the Atacama Large Millimeter/sub-millimeter Array (ALMA) to study the SFE in the bulge of the AGN-host galaxy NGC 3169. After distinguishing star-forming regions from AGN-ionized regions using emission-line ratio diagnostics, we measure spatially resolved molecular gas depletion times (τdep ≡1/SFE) with a spatial resolution of ≈100 pc within a galactocentric radius of 1.8 kpc. We identify a star-forming ring located at radii 1.25 ± 0.6 kpc with an average τdep of 0.3 Gyr. At radii <0.9 kpc, however, the molecular gas surface densities and depletion times increase with decreasing radius, the latter reaching approximately 2.3 Gyr at a radius ≈500 pc. Based on analyses of the gas kinematics and comparisons with simulations, we identify AGN feedback, bulge morphology and dynamics as the possible causes of the radial profile of SFE observed in the central region of NGC 3169.